ERP Systems and Management Accounting: New Understandings through "Nudging" in Qualitative Research - Spraakman,Gary; O’Grady,Winifred; Askarany,Davood; Akroyd,Chris (Journal of Accounting & Organizational Change, 2018)
Purpose: This paper aims to show how our understanding of the effects of enterprise resource planning (ERP) systems on management accounting are influenced through “nudging” by researchers in their preamble before interviews begin. Design/methodology/approach: There were two groups of comparable respondents. Each group received a different preamble to the same questions. The differences in group responses were analyzed. Findings: When the impact of ERP implementation on the physical, transactional and information flows within the firm were nudged, the responses focused on how the chart of accounts had to be expanded to account for the additional data introduced by transaction processing. When the IT and ERP system knowledge and skills were nudged, the responses tended to emphasize analyses or the use of new information through the use of drill down functionality. This research provides new insights and contributions to understanding how nudging affects or directs respondent assessments of the impact of ERP systems on management accounting. Research limitations/implications: The research is limited by the relatively small samples and by the fact that these were different research projects. Practical implications: Nudging has an obvious impact on research that should not be ignored. Social implications: Unintentional nudging should be considered with all research projects. Originality/value: This paper makes explicit that nudging occurs in research whether intentional or unintentional.
Keywords: Accounting

Employers' Perceptions of Information Technology Competency Requirements for Management Accounting Graduates - Spraakman,Gary; O’Grady,Winifred; Askarany,Davood; Akroyd,Chris (Accounting Education, 2015)
Management accountants work in a computerized workplace with information technology (IT) being used for financial ledgers and reporting. Thus, the role of the management accountant has shifted from capturing and recording transactions to analyzing business issues. This paper examines the IT knowledge and skills that employers require of management accounting graduates. An exploratory field research approach was used to gather data. Chief financial officers (CFOs) and their subordinates at some of New Zealand’s largest firms were interviewed. These respondents were consistent in their requirements. In particular they emphasized intermediate proficiency with some Microsoft tools (Excel, Word, PowerPoint, and Outlook) and familiarity with the structure and navigation of an enterprise resource planning (ERP) system to be able to process transactions such as accounts receivable or accounts payable. Of those requirements, Excel for analysis was by far the most important. Our contributions update and augment the literature by clarifying the perceptions of employers regarding the IT competencies required of management accounting graduates.
Keywords: Accounting